Alteration of serum biochemical parameters and urinalysis in Sprague Dawley rats administered with N-methyl-N-nitrosourea - Hakimi, M. K.; Hamzah, Hazilawati; Shaari, Mohd Rosly; Mohd Zairi, Nurul Huda; M. Y., Yusnani; Sithambaram, Shanmugavelu; Mohamed Mustapha, Noordin; Al-Salih, Hutheyfa A. H. (2012)
Blood serum and urine encompass a wide array of chemical molecules and enzymes that reflect the physiological and pathological states of the body. The deviation of concentration of these parameters exceeding the normal value orchestrates serious clinical signs of the presence of diseases or organs failure. The first objective of this experiment was to study the pattern of changes in concentration of serum biochemical parameters in rats received N-methyl-N-nitrosourea (MNU) via oral and intraperitoneal (IP) routes of administration. Serum enzymes are useful diagnostic tools that act as biomarkers for many diseases including cancers. The concentration of six enzymes with different biological functions was measured and five of them appeared to be significantly increased in MNU-treated rats as compared to untreated counterpart. Potassium (K) levels were also significantly increased in the MNU-treated groups. Uric acid (UA) levels were both increased in the MNU- treated groups but it was only significantly elevated in rats received MNU via oral route. The second objective in this study was to measure the rate of creatinine clearance and urine protein to creatinine ratio of rats administered MNU orally and IP route. The statistical analysis revealed that the rate of creatinine clearance in rats received MNU orally was significantly decreased in comparison with untreated and rats received MNU via IP route.